Exploring the human leukocyte phosphoproteome using a microfluidic reversed-phase-TiO2-reversed-phase high-performance liquid chromatography phosphochip coupled to a quadrupole time-of-flight mass spectrometer. - Raijmakers, R; Kraiczek, K; de Jong, A; Mohammed, S; Heck, A (2010)
The study of protein phosphorylation events is one of the most important challenges in proteome analysis. Despite the importance of phosphorylation for many regulatory processes in cells and many years of phosphoprotein and phosphopeptide research, the identification and characterization of phosphorylation by mass spectrometry is still a challenging task. Recently, we introduced an approach that facilitates the analysis of phosphopeptides by performing automated, online, TiO(2) enrichment of phosphopeptides prior to mass spectrometry (MS) analysis. The implementation of that method on a "plug-and-play" microfluidic high-performance liquid chromatography (HPLC) chip design will potentially open up efficient phosphopeptide enrichment methods enabling phosphoproteomics analyses by a broader research community. Following our initial proof of principle, whereby the device was coupled to an ion trap, we now show that this so-called phosphochip is capable of the enrichment of large numbers of phosphopeptides from complex cellular lysates, which can be more readily identified when coupled to a higher resolution quadrupole time-of-flight (Q-TOF) mass spectrometer. We use the phosphochip-Q-TOF setup to explore the phosphoproteome of nonstimulated primary human leukocytes where we identify 1012 unique phosphopeptides corresponding to 960 different phosphorylation sites providing for the first time an overview of the phosphoproteome of these important circulating white blood cells.